Wintertime pollution level, size distribution and personal daily exposure to particulate matters in the northern and southern rural Chinese homes and variation in different household fuels. (December 2017) - Du, Wei; Shen, Guofeng; Chen, Yuanchen; Zhuo, Shaojie; Xu, Yang; Li, Xinyue; Pan, Xuelian; Cheng, Hefa; Wang, Xilong; Tao, Shu
Abstract: This study investigated and compared wintertime air pollution and personal exposure in the rural northern and southern Chinese homes. Daily indoor and outdoor particle samples were simultaneously collected by using stationary samplers, and personal exposure was directly measured using portable carried samplers. The daily average concentrations of indoor and outdoor PM2.5 were 521 ± 234 and 365 ± 185 μg/m 3 in the northern village, that were about 2.3–2.7 times of 188 ± 104 and 150 ± 29 μg/m 3 in indoor and outdoor air in the southern villages. Particle size distribution was similar between indoor and outdoor air, and had relatively smaller difference between the two sites, relative to the particle mass concentration difference. PM2.5 contributed to ∼80% of the TSP mass, and in PM2.5, near 90% were PM1.0 . In homes using electricity in the southern villages, outdoor air pollution could explain 70–80% of the variation in indoor air pollution. The daily exposure to PM2.5 measured using personal carried samplers were 451 ± 301 μg/m 3 in the northern villages with traditional solid fuels used for daily cooking and heating, and in the southern villages without heating, the exposure to PM2.5 were 184 ± 83 and 166 ± 45 μg/m 3, respectively, for the population using wood and electricity for daily cooking. Time-weighted daily average exposure estimated from area concentration and time spent indoor and outdoor was generally correlated the directly measured exposure. Graphical abstract: Highlights: Indoor concentration was ∼50% higher than the outdoor level when solid fuels were burned. In homes using electricity indoor and outdoor particle concentrations were comparable. Outdoor air pollution explained 70-80% of variations in indoor air pollution in homes using electricity. The pollution levels in the northern village were 2–3 times of that in the southern village. The mass of PM1.0 comprised up to near 90% of the PM2.5 mass. Abstract : Differentiating pollution levels and indoor-outdoor relationship in particulate matters in rural homes in the northern and southern areas with/without solid fuels for heating, and much lower HAP levels and human exposure for the residents using electricity.